Semejanzas y diferencias entre el Movimento 5 stelle y Podemos - Rodríguez-Aguilera de Prat, Cesáreo (SocietàMutamentoPolitica, 2015)
The severe economic crisis that began in 2008 has encouraged the new emergence of protest parties in some European countries. The erosion of traditional politics has been capitalized by populist oriented movements: in the Italian case the Movimento 5 Stelle and in the Spanish case Podemos. The goal of this contribution is the analysis of the causes, organizational trajectories, leadership structures, social bases and ideological and programmatic issues of both parties. The M5S and Podemos have strategic and ideological differences, but share the radical criticism of the “system” which they disqualify outright.